Accurate radiographic interpretation of misfit milled zirconia crowns of different designs: An in vitro study - Mohammad Barayan; Khadijah M. Baik (PLoS ONE, 2026)
Prosthodontists often assess crown margins clinically and radiographically. However, judging an open crown margin clinically is difficult, and their radiographic assessment is controversial. The objective of this study was to investigate factors influencing interpretation of crown margins to optimize their assessment. Nine plastic KaVo model teeth were divided into three groups (n = 3 per group), and each group received a different margin design (slanted buccal or lingual, concave coronal or convex, 0.7 mm or 1 mm finish line). Zirconia crowns were fabricated, and preparations were exposed to five different radiographic angulations: 1) perpendicular to both the plate and teeth; 2) with 10° of mesial shift; 3) with 10° of distal shift; 4) with +10° vertical angulation; and 5) with −10° vertical angulation. Images were interpreted for open/closed margins by three consultants. Binary logistic regression was used to determine predictors of an open margin, and intra- and inter-examiner reliability was assessed. Overall, closed margins (false negatives) were most detected when the PID was at +10° vertical angulation (72.2% of the time), independent of margin design. Predictors of an open crown margin were position-indicating device (PID) angles at right angles to the tooth and 10° mesial shift when the margin was 0.7 mm. However, it was less likely that a slanted buccal open crown margin would be detected with +10° vertical angulation. The radiographic interpretation of the margins of zirconia crowns is significantly influenced by PID angulation and margin design. A + 10° vertical angulation should be avoided when assessing marginal adaptation, and a convex coronal finish line of <1 mm should be avoided as they are harder to detect radiographically when open.